The Evolving Role of Triage and Appointment-Based Admission to Improve Service, Care and Outcomes in Animal Shelters - Hurley, Kate F. (Frontiers in Veterinary Science, 2022)
The historical norm for many animal shelters has been to admit animals on an unscheduled basis, without prior assessment of animal or client need or regard to the shelter’s ability to deliver humane care or ensure appropriate outcomes. This approach allows little opportunity to provide finders or owners with alternatives to keep pets safe in their homes or community rather than being impounded. In addition to needlessly impounding animals and separating pets from families, unmanaged/unscheduled admission frequently results in animal influx exceeding shelter capacity, leading to crowding, stress, disease, and euthanasia of animals, as well as poor customer experience, compromised staffing efficiency and decreased organizational effectiveness. Many of these harmful consequences disproportionately impact vulnerable community members and their pets. Triage and appointment-based services have been well developed in healthcare and other service sectors allowing organizations to prioritize the most urgent cases, align services with organizational resources and provide situation-specific solutions that may include virtual support or referral as appropriate. This article discusses the trend in animal sheltering towards triage and appointment-based services that parallels the use of these practices in human healthcare. Reported positive results of this approach are detailed including improved staff morale, reduced disease rates and substantially reduced euthanasia. These positive outcomes support the endorsement of triage and appointment-based services by multiple North American animal welfare professional and academic organizations, recognizing that it better realizes the goals of shelters to serve the common good of animals and people in the most humane, equitable and effective possible way.